A core-shell structured lithium-rich manganese-based positive electrode material and preparation method thereof
By adopting a core-shell structure of lithium-rich manganese-based positive electrode material, and synthesized by co-precipitation method and sol-gel method, the problems of low efficiency, poor cycle stability and poor rate performance of traditional lithium-rich manganese-based positive electrode material are solved, and higher electrochemical performance is achieved.
Patent Information
- Application Number
- CN202211193556.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-09-28
AI Technical Summary
Traditional lithium-rich manganese-based positive electrode materials have problems such as low efficiency, poor cycle stability and poor rate performance in the first circle, which limits the application of lithium-ion batteries.
A lithium-rich manganese-based positive electrode material adopts a core-shell structure. Its inner core is a co-precipitated oxalate precursor and a lithium-rich positive electrode material. It is synthesized by co-precipitation method and sol-gel method to form uniform spherical particles of 100nm-200nm.
The specific surface area and rate performance of the material are improved, the embedded capacity of lithium ions is enhanced, and the impact of spinel phase transformation on electrochemical performance is reduced, thereby improving the first charging efficiency and cycling performance.
Smart Images

Figure CN115498159B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a lithium-rich manganese-based positive electrode material with a core-shell structure and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have become the mainstream product in secondary batteries at this stage. They are widely used in portable electronic devices such as smart phones and notebooks, and are driving industrial upgrades and changes in fields such as new energy vehicles and large-scale energy storage. However, the specific energy density of lithium-ion batteries is still relatively low. The fundamental reason that limits the promotion of lithium-ion batteries is the positive electrode material. Therefore, developing a new generation of positive electrode materials with high specific energy, green environmental protection and low cost has become one of the main research directions. LiCoO2, LiMn2O4, LiNiO2 and LiFePO4 are all common commercial positive electrode materials today, but the specific capacity of these positive electrode materials is less than 200mAh / g. Lithium-rich positive electrode materials have ultra-high capacity (250mAh / g), but they have voltage attenuation problems. Therefore, finding a high-capacity and structurally stable lithium battery positive electrode material is a major task in the current lithium battery research field.
[0003] As an important component of the battery, traditional lithium-rich manganese-based positive electrode materials have three main disadvantages: low first-cycle coulombic efficiency (<80%), poor cycle stability and rate performance. These three disadvantages are the main obstacles for them to dominate the field of commercial power batteries. For this reason, we proposed a core-shell structured lithium-rich manganese-based positive electrode material and its preparation method. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a core-shell structured lithium-rich manganese-based positive electrode material and a preparation method thereof, which solves the above-mentioned problems.
[0006] (II) Technical solution
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a core-shell structured lithium-rich manganese-based positive electrode material, comprising Mn as a crystal core α M β C2O2·2H2O and Li as the outer shell 1+x Mn y M z O2, Mn α M β C2O2·2H2O includes 0.5-5mol / L metal salt A solution and 0.5-5mol / L precipitant solution, Li 1+x Mn y M zO2 includes 1-5 mol / L metal salt B solution and chelating agent solution;
[0008] Mn α M β C2O2·2H2O:Li 1+x Mn y M z The molar ratio of O2 is 1-10:30;
[0009] Mn α M β C2O2·2H2O and Li 1+x Mn y M z In O2, 0<x≤0.3, 0<z≤0.5, 0.5≤y≤1, x+y+z=1, 0<α≤1, 0<β≤1, α+β=1.
[0010] Preferably, 0.5≤y≤0.8, and M is Ni.
[0011] Preferably, the precipitant is selected from at least one of oxalic acid and ammonium oxalate;
[0012] The metal salt A solution includes a manganese salt and a substance M;
[0013] The metal salt B solution includes: manganese salt, organic solvent, M substance and lithium salt;
[0014] The chelating agent is selected from at least one of citric acid and maleic acid.
[0015] Preferably, the manganese salt is at least one of manganese acetate and manganese sulfate;
[0016] The substance M is at least one of nickel acetate and nickel sulfate;
[0017] The lithium salt is at least one of lithium acetate, lithium nitrate, lithium sulfate and lithium chloride;
[0018] The organic solvent is at least one of isopropyl alcohol and ethylene glycol.
[0019] Preferably, the Mn α M β C2O2·2H2O and Li 1+x Mn y M z M in O2 includes at least one of Mg, Al, Cr, Fe, Co, Ni, Cu, Zn, Zr, Nb, and Mo.
[0020] A method for preparing a lithium-rich manganese-based positive electrode material with a core-shell structure, comprising the following steps:
[0021] Step 1: dissolve manganese salt and substance M in water to obtain metal salt A solution;
[0022] Step 2: dissolving the precipitant in water to obtain a precipitant solution;
[0023] Step 3: Slowly drip the metal salt A solution into the precipitant solution to form oxalate co-precipitation, and then wash and dry at constant temperature to obtain Mn α M β C2O2·2H2O precursor, the molar ratio of the precipitant to the metal element in the metal A solution is 1.2-1.8:1;
[0024] Step 4: dissolving the manganese salt, M substance and lithium salt in a mixture of water and an organic solvent to obtain a metal salt B solution;
[0025] Step 5: Dissolve the chelating agent in water. After it is completely dissolved, add Mn α M β The C2O2·2H2O precursor is prepared into an acid mixed solution with a concentration of 1-5 mol / L;
[0026] Step 6: Drop the metal salt B solution into the acid solution and react at a constant temperature of 70-90°C to prepare a sol;
[0027] Step 7: Dry the sol under vacuum to obtain gel, and grind the gel to obtain gel powder;
[0028] Step 8: calcining the gel powder to obtain spherical particles with a core-shell structure of lithium-rich manganese-based positive electrode materials with a particle size of 100nm-200nm.
[0029] Preferably, the constant temperature washing and drying reaction conditions in the third step are constant temperature reaction at 40-90° C. for 0.5-12 h, filtration and washing, and drying at 70-200° C. for 6-48 h.
[0030] Preferably, the drying reaction in the seventh step is carried out at 160-220° C. for 15-24 hours.
[0031] Preferably, the calcination in the eighth step is carried out at 800-900° C. for 8-24 hours.
[0032] Preferably, the molar ratio of the precipitant to the metal element in the metal A solution is 1.2-1.5:1.
[0033] Preferably, the molar ratio of the chelating agent to the metal ions in the metal B solution is 1.03-1.1:1.
[0034] Preferably, the amount of lithium ions added during the preparation of the lithium salt needs to be greater than 3-10% of the molar ratio of the chemical formula.
[0035] (III) Beneficial effects
[0036] Compared with the prior art, the present invention provides a core-shell structured lithium-rich manganese-based positive electrode material and a preparation method thereof, which has the following beneficial effects:
[0037] 1. The core-shell structured lithium-rich manganese-based cathode material and its preparation method are composite materials with a co-precipitated oxalate precursor as the core and a lithium-rich cathode material as the shell. Compared with traditional lithium-rich materials, the Mn α M β C2O2 decomposes CO, CO2 and other gases during high-temperature calcination, making the material particles more dispersed and effectively alleviating the serious problem of material agglomeration. The material particles reach 100nm, and the uniform spherical small particles increase the specific surface area of the material, which is more fully in contact with the electrolyte and can improve the rate performance of the material.
[0038] 2. The core-shell structured lithium-rich manganese-based positive electrode material and its preparation method, the core precursor Mn α M β C2O2 forms Mn after high temperature calcination α M β O2, its interior is in a lithium-deficient state. When the lithium-rich material in the outer shell occupies lithium ion vacancies due to phase change, the inner core can provide lithium ion vacancies, allowing more lithium ions to be embedded in the material, reducing the impact of the spinel phase change on the electrochemical properties of the material, thereby improving the material's first charge efficiency and cycle performance.
[0039] 3. The lithium-rich manganese-based positive electrode material with a core-shell structure and its preparation method, the oxalate precursor is prepared by a co-precipitation method, and then the lithium-rich manganese-based positive electrode material with a core-shell structure is synthesized by a sol-gel method. Compared with the core-shell structure positive electrode material prepared by the co-precipitation-co-precipitation method, the co-precipitation method of the present invention only reaches the precursor preparation stage, and there is no further addition of lithium salt calcination, which reduces the preparation time and reduces energy loss. The sol-gel method has mild reaction conditions, a simple preparation method, and can achieve molecular or atomic level mixing of raw materials, so the obtained material particles are uniform and fine, which is convenient for industrial large-scale production. The present invention adopts co-precipitation combined with the sol-gel method, which has the advantages of simple synthesis process, easy control, good repeatability, etc., and has great commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The SEM images of the positive electrode materials of lithium ion batteries prepared in Example 1 and Comparative Example 1 of the present invention;
[0041] Figure 2 XRD pattern of the material prepared in Example 1 of the present invention;
[0042] Figure 3The first cycle charge and discharge curves of the positive electrode materials of lithium ion batteries prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention at a rate of 20 mA / g;
[0043] Figure 4 The constant current charge and discharge performance diagrams of the lithium ion battery positive electrode materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention at different rates;
[0044] Figure 5 This is a cycle performance diagram of the lithium ion battery positive electrode materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention at 1C rate. DETAILED DESCRIPTION
[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] See also Figure 1-5 , a lithium-rich manganese-based positive electrode material with a core-shell structure. The specific preparation process is detailed in the following Examples 1 to 3.
[0047] Example 1
[0048] The core-shell structure of lithium-rich manganese-based cathode material has a general chemical formula of 2Mn 0.75 Ni 0.25 O2-30Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2;
[0049] The preparation method of a lithium-rich manganese-based positive electrode material with a core-shell structure comprises the following steps:
[0050] S1, weighing manganese sulfate monohydrate and nickel sulfate hexahydrate according to the stoichiometric ratio, dissolving them in distilled water, stirring at room temperature to completely dissolve them, and preparing a metal A solution with a concentration of 1 mol / L;
[0051] S2, weigh ammonium oxalate according to a certain ratio and dissolve it in distilled water, stir it at room temperature to make it completely dissolved, and prepare a precipitant solution with a concentration of 1 mol / L. The molar ratio of transition metal A: ammonium oxalate is 1:1.4;
[0052] S3, slowly drip the metal A solution into the ammonium oxalate solution, stir at 50°C and 1200 rpm for 1 hour, filter, wash twice with ethanol and distilled water respectively, and dry in a forced air oven at 80°C for 12 hours to obtain a coprecipitation precursor;
[0053] S4, weighing manganese acetate tetrahydrate, lithium acetate dihydrate, nickel acetate tetrahydrate, and cobalt acetate tetrahydrate according to the stoichiometric ratio, dissolving them in distilled water, stirring at room temperature to completely dissolve them, and preparing a metal B solution with a concentration of 2 mol / L, wherein lithium acetate dihydrate is in excess of 5% by molar ratio;
[0054] S5, dissolving a certain ratio of citric acid in a mixture of deionized water and ethylene glycol (1:1v), stirring at room temperature to completely dissolve it, and then adding an appropriate amount of coprecipitation precursor, stirring and ultrasonicating for 30 minutes to prepare a citric acid solution with a concentration of 2 mol / L. The molar ratio of citric acid to the metal ions in the metal B solution is 1.05:1, and the shell Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 The molar ratio of the O2 material to the coprecipitated precursor is 15:1;
[0055] S6, slowly dripping the prepared metal B solution into the citric acid solution, reacting at a constant temperature of 80°C, and continuously stirring until it is in a sol state, thereby preparing a sol;
[0056] S7, placing the prepared sol in a vacuum oven, drying at 180° C. for 24 hours under vacuum, evaporating the sol to dryness, and preparing a gel;
[0057] S8, placing the ground gel powder in a muffle furnace and calcining at 850° C. for 20 hours at a heating rate of 5° C. / min to obtain a lithium-rich manganese-based positive electrode material with a core-shell structure;
[0058] Example 2
[0059] The core-shell structure of lithium-rich manganese-based cathode materials has the general chemical formula of 4Mn 0.75 Ni 0.25 O2-30Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2.
[0060] The preparation method of a lithium-rich manganese-based positive electrode material with a core-shell structure comprises the following steps:
[0061] S1, weighing manganese sulfate monohydrate and lithium sulfate hexahydrate according to the stoichiometric ratio, dissolving them in distilled water, stirring at room temperature to completely dissolve them, and preparing a metal A solution with a concentration of 1 mol / L;
[0062] S2, weigh ammonium oxalate according to a certain ratio and dissolve it in distilled water, stir it at room temperature to make it completely dissolved, and prepare a precipitant solution with a concentration of 1 mol / L. The molar ratio of transition metal A: ammonium oxalate is 1:1.4;
[0063] S3, slowly drip the metal A solution into the ammonium oxalate solution, stir at 50°C and 1200 rpm for 1 hour, filter, wash twice with ethanol and distilled water respectively, and dry in a forced air oven at 80°C for 12 hours to obtain a coprecipitation precursor;
[0064] S4, weighing manganese acetate tetrahydrate, lithium acetate dihydrate, nickel acetate tetrahydrate, and cobalt acetate tetrahydrate according to the stoichiometric ratio, dissolving them in distilled water, stirring at room temperature to completely dissolve them, and preparing a metal B solution with a concentration of 2 mol / L, wherein lithium acetate dihydrate is in excess of 5% by molar ratio;
[0065] S5, dissolving a certain ratio of citric acid in a mixture of deionized water and ethylene glycol (1:1v), stirring at room temperature to completely dissolve it, and then adding an appropriate amount of coprecipitation precursor, stirring and ultrasonicating for 30 minutes to prepare a citric acid solution with a concentration of 2 mol / L. The molar ratio of citric acid to the metal ions in the metal B solution is 1:1, and the shell Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 The molar ratio of the O2 material to the coprecipitated precursor is 15:2;
[0066] S6, slowly dripping the prepared metal B solution into the citric acid solution, reacting at a constant temperature of 80°C, and continuously stirring until it is in a sol state, thereby preparing a sol;
[0067] S7, placing the prepared sol in a vacuum oven, drying at 180° C. for 24 hours under vacuum, evaporating the sol to dryness, and preparing a gel;
[0068] S8, placing the ground gel powder in a muffle furnace and calcining at 850° C. for 20 hours at a heating rate of 5° C. / min to obtain a lithium-rich manganese-based positive electrode material with a core-shell structure;
[0069] Example 3
[0070] The core-shell structure of lithium-rich manganese-based cathode materials has the general chemical formula of 1Mn 0.75 Ni 0.25 O2-30Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2.
[0071] The preparation method of a lithium-rich manganese-based positive electrode material with a core-shell structure comprises the following steps:
[0072] S1, weighing manganese sulfate monohydrate and lithium sulfate hexahydrate according to the stoichiometric ratio, dissolving them in distilled water, stirring at room temperature to completely dissolve them, and preparing a metal A solution with a concentration of 1 mol / L;
[0073] S2, weigh ammonium oxalate according to a certain ratio and dissolve it in distilled water, stir it at room temperature to make it completely dissolved, and prepare a precipitant solution with a concentration of 1 mol / L. The molar ratio of transition metal A: ammonium oxalate is 1:1.4;
[0074] S3, slowly drip the metal A solution into the ammonium oxalate solution, stir at 50°C and 1200 rpm for 1 hour, filter, wash twice with ethanol and distilled water respectively, and dry in a forced air oven at 80°C for 12 hours to obtain a coprecipitation precursor;
[0075] S4, weighing manganese acetate tetrahydrate, lithium acetate dihydrate, nickel acetate tetrahydrate, and cobalt acetate tetrahydrate according to the stoichiometric ratio, dissolving them in distilled water, stirring at room temperature to completely dissolve them, and preparing a metal B solution with a concentration of 2 mol / L, wherein lithium acetate dihydrate is in excess of 5% by molar ratio;
[0076] S5, dissolving a certain ratio of coprecipitation precursor and citric acid in a mixture of deionized water and ethylene glycol (1:1v), stirring at room temperature to completely dissolve, and then adding an appropriate amount of coprecipitation precursor, stirring and ultrasonicating for 30 minutes to prepare a citric acid solution with a concentration of 2 mol / L. The molar ratio of citric acid to the metal ions in the metal B solution is 1:1, and the shell Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 The molar ratio of the O2 material to the coprecipitated precursor is 15:3;
[0077] S6, slowly dripping the prepared metal B solution into the citric acid solution, reacting at a constant temperature of 80°C, and continuously stirring until it is in a sol state, thereby preparing a sol;
[0078] S7, placing the prepared sol in a vacuum oven, drying at 180° C. for 24 hours under vacuum, evaporating the sol to dryness, and preparing a gel;
[0079] S8, placing the ground gel powder in a muffle furnace and calcining at 850° C. for 20 hours at a heating rate of 5° C. / min to obtain a lithium-rich manganese-based positive electrode material with a core-shell structure;
[0080] Comparative Example 1
[0081] A traditional lithium-rich manganese-based cathode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2.
[0082] The method for preparing the above-mentioned lithium-rich manganese-based positive electrode material comprises the following steps:
[0083] S1, weighing manganese acetate tetrahydrate, lithium acetate dihydrate, nickel acetate tetrahydrate, and cobalt acetate tetrahydrate according to the stoichiometric ratio, dissolving them in distilled water, stirring at room temperature to completely dissolve them, and preparing a metal solution with a concentration of 2 mol / L, wherein lithium acetate dihydrate is in excess of 5% by molar ratio;
[0084] S2, dissolving a certain ratio of citric acid in a mixture of deionized water and ethylene glycol (1:1v), stirring at room temperature to completely dissolve it, and preparing a citric acid solution with a concentration of 2 mol / L. The molar ratio of citric acid to the metal ions in the metal solution is 1:1;
[0085] S3, slowly dripping the prepared metal solution into the citric acid solution, reacting at a constant temperature of 80°C, and continuously stirring until the solution is in a sol-like state, thereby preparing a sol;
[0086] S4, placing the prepared sol in a vacuum oven, drying at 180° C. for 24 hours under vacuum, evaporating the sol to dryness, and preparing a gel;
[0087] S5, placing the ground gel powder in a muffle furnace and calcining it at 850° C. for 20 hours at a heating rate of 5° C. / min to obtain a lithium-rich manganese-based positive electrode material with a core-shell structure;
[0088] Performance Testing
[0089] 1. Microstructure characterization:
[0090] The lithium ion battery positive electrode materials prepared in Example 1 and Comparative Example 1 were subjected to SEM analysis, and the results are as follows: Figure 1 As shown in the figure, the material is a uniform small nano-sized particle with a particle size of 100nm-200nm, but the material agglomeration of comparative example 1 is more serious. XRD characterization of Example 1 is performed, as shown in FIG. Figure 2 As shown, except for the superlattice peak at 20-30°, the spectrum conforms to the R-3m space group structure and has high crystallinity.
[0091] 2. Lithium-ion battery performance:
[0092] The lithium-ion battery positive electrode materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were weighed with super carbon black and PVDF at a mass ratio of 8:1:1, ground for 15 minutes, stirred and mixed evenly with N-methylpyrrolidone (MNP) as a solvent, and then coated on a dry aluminum foil with a coating thickness of 100 μm, and then placed in a vacuum drying oven at 80°C for 24 hours. After taking it out, it was rolled on a rolling machine for 3 times and then cut into electrode discs. This was used as the positive electrode sheet, a metal lithium sheet was used as the negative electrode sheet, a polyethylene (PE) microporous diaphragm, an electrolyte of 1 mol / L LiPF6, ethylene carbonate (EC): diethyl carbonate (DEC) = 1:1, and button batteries were assembled in an argon glove box with a water oxygen value of less than 0.1 ppm and tested on the Xinwei battery test system at room temperature 25°C.
[0093] Conduct lithium-ion battery performance testing: Figure 3 As shown, the battery was first activated for 2 cycles at a rate of 0.1C (1C = 200mAh / g), and the first-cycle coulomb efficiency of the material was tested. The first-cycle charging capacity of Comparative Example 1 was 336mAh / g, the first-cycle discharge capacity was 247mAh / g, the first-cycle coulomb efficiency was 73.5%, and the first-cycle capacity loss was 89mAh / g. The first-cycle charging capacity of Example 1 was 317mAh / g, the first-cycle discharge capacity was 269mAh / g, the first-cycle coulomb efficiency was 84.9%, and the first-cycle capacity loss was 48mAh / g. The first-cycle charging capacity of Example 2 was 293mAh / g, the first-cycle discharge capacity was 252mAh / g, the first-cycle coulomb efficiency was 86.0%, and the first-cycle capacity loss was 41mAh / g. Compared with Comparative Example 1, the core-shell structured lithium-rich manganese-based positive electrode material of Example 1 improves the material's specific charging capacity, while reducing the irreversible loss of capacity and improving the first-cycle coulomb efficiency.
[0094] like Figure 4 As shown, the discharge capacities of the battery assembled with the lithium ion battery positive electrode material prepared in Example 1 at 0.1C, 0.5C, 1C, 2C, 3C, and 5C are 269mAh / g, 215mAh / g, 185mAh / g, 152mAh / g, 134mAh / g, and 110mAh / g, respectively, while the discharge capacities of the battery assembled with the lithium ion battery positive electrode material of Comparative Example 1 are 247mAh / g, 196mAh / g, 170mAh / g, 144mAh / g, 130mAh / g, and 107mAh / g, respectively, which indicates that the core-shell structured lithium-rich manganese-based positive electrode material prepared by the present invention has better rate performance than traditional lithium-rich materials.
[0095] like Figure 5As shown, the batteries assembled with the lithium ion battery positive electrode materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were cycled 100 times at 1C. The capacity retention rate of Example 1 was as high as 95.6%, while the capacity retention rate of the material in Comparative Example 1 was only 85.9%, which indicates that Mn 0.75 Ni 0.25 The addition of O2 core effectively improves the cycle performance of lithium-rich manganese-based positive electrode materials.
[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A lithium-rich manganese-based positive electrode material with a core-shell structure, characterized in that: Including Mn as a crystal nucleus α M β C2O2·2H2O and Li as the outer shell 1+x Mn y M z O2 is prepared from 0.5-5 mol / L metal salt A solution, 0.5-5 mol / L precipitant solution, 1-5 mol / L metal salt B solution and chelating agent solution; The metal salt A solution includes a manganese salt and a substance M; The metal salt B solution includes a manganese salt, an organic solvent, an M substance and a lithium salt; The Mn α M β C2O2·2H2O and Li 1+x Mn y M z M in O2 includes at least one of Mg, Al, Cr, Fe, Co, Ni, Cu, Zn, Zr, Nb, and Mo; Mn α M β C2O2·2H2O:Li 1+x Mn y M z The molar ratio of O2 is 1-10:30; Mn α M β C2O2·2H2O and Li 1+x Mn y M z In O2, 0<x≤0.3, 0<z≤0.5, 0.5≤y <1, x+y+z=1, 0<α<1, 0<β<1, α+β=1.
2. A core-shell structured lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: 0.5≤y≤0.8, M is Ni.
3. The core-shell structured lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The precipitant is selected from at least one of oxalic acid and ammonium oxalate; The chelating agent is selected from at least one of citric acid and maleic acid.
4. A core-shell structured lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The manganese salt is at least one of manganese acetate and manganese sulfate; The substance M is at least one of nickel acetate and nickel sulfate; The lithium salt is at least one of lithium acetate, lithium nitrate, lithium sulfate and lithium chloride; The organic solvent is at least one of isopropyl alcohol and ethylene glycol.
5. A method for preparing the core-shell structured lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The following steps are involved: Step 1: dissolve manganese salt and substance M in water to obtain metal salt A solution; Step 2: dissolving the precipitant in water to obtain a precipitant solution; Step 3: Slowly drip the metal salt A solution into the precipitant solution to form oxalate co-precipitation, and then wash and dry at constant temperature to obtain Mn α M β C2O2·2H2O precursor, the molar ratio of the precipitant to the metal element in the metal A solution is 1.2-1.8:1; Step 4: dissolving the manganese salt, M substance and lithium salt in a mixture of water and an organic solvent to obtain a metal salt B solution; Step 5: Dissolve the chelating agent in water. After it is completely dissolved, add Mn α M β A C2O2·2H2O precursor is prepared into an acid mixed solution with a chelating agent concentration of 1-5 mol / L, wherein the chelating agent is selected from at least one of citric acid and maleic acid; Step 6: Drop the metal salt B solution into the acid mixed solution and react at a constant temperature of 60-90°C to prepare a sol; Step 7: Dry the sol under vacuum to obtain gel, and grind the gel to obtain gel powder; Step 8: calcining the gel powder to obtain a spherical core-shell structured lithium-rich manganese-based positive electrode material with a particle size of 100nm-200nm.
6. The method for preparing a lithium-rich manganese-based positive electrode material with a core-shell structure according to claim 5, characterized in that: The constant temperature washing and drying reaction conditions in the third step are constant temperature reaction at 40-90°C for 0.5-12h, filtration and washing, and drying at 70-200°C for 6-48h; The drying reaction in the seventh step is drying at 160-220° C. for 15-24 hours; The calcination in the eighth step is carried out at 800-900° C. for 8-24 hours.
7. The method for preparing a core-shell structured lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The molar ratio of the precipitant to the metal element in the metal salt A solution is 1.2-1.5:
1.
8. The method for preparing a core-shell structured lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The molar ratio of the chelating agent in the acid mixed solution to the metal ions in the metal salt B solution is 1.03-1.1:
1.
9. The method for preparing a core-shell structured lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The amount of lithium ions added during the preparation of the lithium salt must be greater than the amount of Li 1+x Mn y M z 3-10% of the molar ratio of Li in the O2 chemical formula.